A case series of ventricular cystic masses. Issue 6 (7th December 2020) - Tong, Jieli; Low, Randal Jun Bang; Joseph Francis, Prabath; Ong, Paul Jau Lueng; Lee, Evelyn Min
Abstract: Background: Ventricular cystic masses are uncommon. Elucidating the cause is essential for early directed therapy and prevention of complications. We present two cases of ventricular cystic masses, one in each ventricle, after myocardial infarction (MI) and ventricular septal rupture (VSR), respectively. Case summary: Patient 1 is a 58-year-old male with left brachio-facial stroke and evolved anterior MI. A left ventricular (LV) cystic thrombus was seen on transthoracic echocardiogram (TTE) and cardiac magnetic resonance (CMR) imaging. He was started on anticoagulation with reduction in thrombus size 11 days later. Patient 2 is a 67-year-old male with evolved anterior MI, severe LV systolic dysfunction, and normal right ventricular (RV) function. He was readmitted two weeks later with fever, heart failure, Streptococcus agalactiae bacteraemia, and septic pulmonary emboli. Transthoracic echocardiogram showed biventricular systolic dysfunction and a RV cystic mass associated with a partial VSR. He was treated with anticoagulation and antibiotics. Repeat TTE 5 weeks later revealed near resolution of the cystic mass and complete VSR. Cardiac magnetic resonance confirmed these findings and also showed a localized mid-septal transmural infarction at the VSR site. He underwent percutaneous coronary intervention to the left anterior descending and circumflex arteries, and percutaneous VSR closure with a muscular ventricular septal defect device later. Discussion: Our two cases demonstrate that ventricular thrombi can present as cystic masses after MI and VSRs. Infectious, vascular, or oncogenic causes should be considered in the appropriate clinical context. Early diagnosis and treatment is essential to prevent embolic complications, and secondary infection.